Soils and carbon distribution at Byers Peninsula - Maritime Antarctica, based on the climate change scenario - THIAGO T.C. PEREIRA; JOSÉ JOÃO L.L. DE SOUZA; MÁRCIO R. FRANCELINO; ELPÍDIO INÁCIO FERNANDES FILHO; CARLOS ERNESTO G.R. SCHAEFER (Anais da Academia Brasileira de Ciências, 2025)
Abstract Maritime Antarctica has a milder climate than the Antarctic continent and is naturally more sensitive to rising global temperature. Therefore, it is necessary to understand the soils, including those with permafrost, as well as the relief and the occurrence of organic carbon at Byers Peninsula. This study aims therefore to investigate soil physical and chemical properties at Byers Peninsula, Maritime Antarctica, in particular, the distribution of organic carbon. Thirteen soil profiles were described, collected, and subjected to a physical, chemical, and spatial analysis. Colonization by avifauna and vegetation is important for inputing soil organic carbon at Byers Peninsula. Cryoturbation and permafrost are crucial for the redistribution of the C pool. Distribution of organic carbon on the Byers Peninsula have shown that its concentrations are higher and more punctual at the surface, but also that carbon has been redistributed to deeper layers. Gelisols (Cryosols) are important C pools. They are extremely useful from the environmental monitoring perspective as they represent areas sensitive to temperature increases on the Antarctic Peninsula caused by global climate changes. Using geomorphological groups is one way to improve the understanding of these relief forms, soil and rock types, vegetation patterns, and the presence of permafrost.